Usability of the lateral decubitus position on four-dimensional ultra-low-dose computed tomography for the detection of localized pleural adhesion in the pulmonary apical region - Sato, Shigetaka; Nagatani, Yukihiro; Hashimoto, Masayuki; Nitta, Norihisa; Hanaoka, Jun; Ushio, Noritoshi; Tsukagoshi, Shinsuke; Uranishi, Ayumi; Kimoto, Tatsuya; Oshio, Yasuhiko; Mayumi, Masayuki; Sonoda, Akinaga; et al. (Acta radiologica (1987), 2021)
Localized pleural adhesion (LPA) evaluation in the apical region is difficult even with four-dimensional ultra-low-dose computed tomography (4D-ULDCT) in the supine position due to smaller pleural movements. To assess usability of 4D-ULDCT in the lateral decubitus (LD) position for LPA detection in the apical region. Forty-seven patients underwent 4D-ULDCT of a single respiration cycle with 16-cm coverage of body axis in supine and LD positions with the affected lung uppermost. Intraoperative thoracoscopic findings confirmed LPA presence. A pleural point and a corresponding point on costal outer edge were placed in identical axial planes at end-inspiration. Pleuro-chest wall distance between two points (PCD) was calculated at each respiratory phase. In the affected lung, average change in amount of PCD (PCD ) was compared between patients with and without LPA in total and two sub-groups (non-COPD and COPD, non-emphysematous and emphysematous patients) in supine and non-dependent (ND) LD positions. Receiver operating characteristic (ROC) curve analysis was performed to determine optimal thresholds in PCD for differentiating patients with LPA from those without. In COPD/emphysematous patients and total population, PCD with LPA was smaller than in those without in the supine and NDLD positions for overall, lateral, and dorsal regions. For the lateral region in COPD patients, area under ROC curve (AUC) increased from supine (0.64) to NDLD position (0.81). For the dorsal region in emphysematous patients, AUC increased from supine (0.76) to NDLD position (0.96). 4D-ULDCT in LD position may be useful for LPA detection in apical regions for COPD and/or emphysematous patients.